Vitamin D Supplementation in Tuberculosis Patients: A Cross Sectional Study - Dina Keumala Sari; Nurfida Khairina Arrasyid; Y. S. Harahap (TALENTA Publisher, Universitas Sumatera Utara, 2019)
Previous studies have not been able to show with certainty the effect of vitamin D supplementation in tuberculosis patients. The objective of this study is to determine whether vitamin D supplementation to patients with tuberculosis could influence 25-hydroxyvitamin D (25(OH)D) and calcium serum levels. The results, after 28 days, the vitamin D supplementation showed significant increase of 25(OH)D serum level at the end point (p=0.001), but not for the calcium serum level (p=0.3). The Conclusions is supplementation with 1,000 IU vitamin D per day increased the 25(OH)D serum level but there was no association with the calcium serum level.